1991
DOI: 10.1001/archsurg.1991.01410310090013
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridamole Thallium Scanning in the Evaluation of Coronary Artery Disease in Elective Abdominal Aortic Surgery

Abstract: Dipyridamole thallium scanning was routinely performed on 68 consecutive patients who presented for elective aortic surgery. All 68 patients were judged by clinical assessment to be at low risk for perioperative cardiac complications. In addition, 42 of 68 patients had a history of myocardial infarction, stable angina, or abnormal echocardiographic findings (group 1). Twenty-six of 68 patients did not have a history of myocardial infarction, angina, or abnormal echocardiographic findings (group 2). In group 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“… No. Inducible ischaemia (%) MI/death (%) PPV NPV Vascular surgery 1985 Boucher [ 135 ] 48 16 (33) 3 (6%) 19% (3/16) 100% (32/32) 1987 Cutler [ 136 ] 116 54 (47) 11 (10%) 20% (11/54) 100% (60/60) 1988 Fletcher [ 137 ] 67 15 (22) 3 (4%) 20% (3/15) 100% (56/56) 1988 Sachs [ 138 ] 46 14 (31) 2 (4%) 14%(2/14) 100% (24/24) 1989 Eagle [ 139 ] 200 82 (41) 15 (8%) 16% (13/82) 98% (61/62) 1990 McEnroe [ 140 ] 95 34 (36) 7 (7%) 9% (3/34) 96% (44/46) 1990 Younis [ 141 ] 111 40 (36) 8 (7%) 15% (6/40) 100% (51/51) 1991 Mangano [ 142 ] 60 22 (37) 3 (5%) 5% (1/22) 95% (19/20) 1991 Strawn [ 143 ] 68 n/a 4 (6%) n/a ...…”
Section: Prognosismentioning
confidence: 99%
“… No. Inducible ischaemia (%) MI/death (%) PPV NPV Vascular surgery 1985 Boucher [ 135 ] 48 16 (33) 3 (6%) 19% (3/16) 100% (32/32) 1987 Cutler [ 136 ] 116 54 (47) 11 (10%) 20% (11/54) 100% (60/60) 1988 Fletcher [ 137 ] 67 15 (22) 3 (4%) 20% (3/15) 100% (56/56) 1988 Sachs [ 138 ] 46 14 (31) 2 (4%) 14%(2/14) 100% (24/24) 1989 Eagle [ 139 ] 200 82 (41) 15 (8%) 16% (13/82) 98% (61/62) 1990 McEnroe [ 140 ] 95 34 (36) 7 (7%) 9% (3/34) 96% (44/46) 1990 Younis [ 141 ] 111 40 (36) 8 (7%) 15% (6/40) 100% (51/51) 1991 Mangano [ 142 ] 60 22 (37) 3 (5%) 5% (1/22) 95% (19/20) 1991 Strawn [ 143 ] 68 n/a 4 (6%) n/a ...…”
Section: Prognosismentioning
confidence: 99%
“…[15][16][17] These data also suggest that the increased risk is associated with higher segmental perfusion abnormalities.…”
Section: Mps For Risk Assessment Before Noncardiac Surgerymentioning
confidence: 71%
“…Several other studies have confirmed the value of DTI in cardiac risk stratification [21,57,59,61,94,113,130]. Leppo and colleagues [57] found that, whilst exercise-induced ST-segment changes were not related to postoperative outcome, in patients who demonstrated thallium redistribution the risk of a postoperative cardiac event was 23 times greater than in patients without redistribution.…”
Section: Radionuclear Imagingmentioning
confidence: 88%
“…Cutler [22] Lette [59] Leppo [57] Younis [130] McEnroe [69] Levinson [63] Mangano [74] Lette [61] Reifsnyder [94] Eagle [29] Eagle [28] Strawn [113] Tischler [114] Lalka [56] Smith [111] Leung [62] London [66] Watters [126] Year 197719781991199119911991199319911991perioperative Year 198519911991199119911991 Type of surgery undergoing elective major non-cardiac surgery, but did not find it to be a predictor of postoperative outcome. It would seem from these studies that the exercise ECG is of limited value as a routine screening procedure for identifying at-risk patients, but that it may be of value for subgroups at greater risk of CAD, such as patients undergoing vascular surgery.…”
Section: Ecgmentioning
confidence: 99%